Lotus 1-2-3 simplified, release 2.2 - Bolocan, David; Bolocan, David (Blue Ridge Summit, PA : Windcrest, 1990)
1-2-3 version 2.2 is one of the best spreadsheets software program in the world. The program not only has limitless spreadsheet applications but also has database management and graphics capabilities. 1-2-3 possesses tremendous potential for use in business, for it is literally three powerful programs interrated in one package.
1. What Can Lotus 1-2-3 Do? -- 2. System Requirements and the Installation Program -- 3. The Keyboard and Disk Operating System -- 4. 1-2-3 Basics -- 5. Essential Spreadsheet Commands and Formulas -- 6. Adding Aesthetic Appeal to Your Worksheet -- 7. The Undo Key, Editing Cells, Moving Ranges and Inserting and Deleting Rows and Columns -- 8. Printing Out the Worksheet -- 9. Manipulating Large Worksheets -- 10. Creating Graphs with 1-2-3 -- 11. Printing Graphs -- 12. Database Management -- 13. Advanced Data Commands -- The Lookup, NPV and Standard Deviation Functions -- 15. Constructing a Time Card -- 16. Accounts Receivable and the Date Function -- 17. The Data Fill, Distribution, and Table Commands -- 18. Linking Spreadsheets with Formulas and the File Combine Command -- 19. Matrices and Linear Regression -- 20. Sharing 1-2-3 Files in a Network -- 21. Programming with Macros -- 22. Macro Commands-A Library of Macro Utilities -- 23. Protecting Spreadsheet Data -- 24. Managing Memory and Issuing DOS Commands -- 25. Spreadsheet Applications -- 26. Add-in Applications and the Add-in Menu -- 27. The Always Add-in -- 18. The Macro Library Manager.
Includes bibliographical references and index.
Keywords: LOTUS 1-2-3 (COMPUTER FILE)